Inserç\~ao internacional do agronegócio brasileiro - Rebecca Lima Albuquerque Maranh\~ao; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The urban population growth in developing countries, the middle class expansion and the increase in per capita income have increased the demand for food. This work aims to identify, from the Constant Market Share (CMS) method, the sources of growth of agricultural exports among the main countries that operate in international trade. This paper analyses two periods: i) from 1992 to 2001; and ii) from 2002 to 2013. At the same time, it was studied the following countries: Brazil, Argentina, Germany, France, United States, India and Argentina. It was verified that Brazil and Argentina stood out in the comparison, although the competitiveness has reduced in the time. On the other hand, India has maintained a strong rise, which has been first associated to world growth than to gains in competitiveness. The United States had a growth rate exports lower than the world average, a factor that can be explained by the loss of competitiveness. In European Union, France has lost ground to Germany, which unlike the French economy presented notorious performance in exports. China experienced a decline in its exports in the whole period analyzed, a movement associated to the expansion of domestic market. Finally, the results point to a growing representation of emerging countries with natural resource potential (Brazil, Argentina and India), while developed economies (the United States and European countries) plus China (this country due to its own internal dynamics) lose space in international market.
Keywords: Q17; Q10; F10; 330; foreign trade; growth; agriculture; market share; agribusiness